Yahoo奇摩 網頁搜尋

  1. 昨晚的回答不知何故又被隱了, 簡單回答吧. 令 x = cos(3π/5) 則 cos(9π/5) = 4x^3 - 3x cos(6π/5) = 2x^2 - 1 cos(9π/5) + cos(6π/5) = 0 即      4x^3 + 2x^2 - 3x - 1       =  (x+1)(4x^2 - 2x - 1 ) = 0. 因 π/2 < 3π/5 < π, 故     0 > cos(3π/5) > -1 故 cos(3π/5) = (1-√5)/4.

    分類:科學及數學 > 數學 2021年01月14日

  2. ...sentence with He(subj) Add the original verb after it= come ori.verb That's not the past tense as it is...: make, let, have. eg:-usage of let eg:- let is to allow sb to do sth eg:- Let them splash around...

    分類:社會及文化 > 語言 2020年10月22日